Aspectos técnicos e interpretativos na peça Matinta e o Curupira para violino solo, de Marcos Salles - Webster Martins De Freitas (2023)
This work came from the interest in playing Brazilian music for the violin. Our object of study is the piece Matinta e o Curupira for solo violin, by the baiano/paraense composer, Marcos Raggio de Salles (1885-1965). First, we sought to situate Salles life and work within the historical context, highlighting the presence of the Amazonian imagination in his musical production. Based on the composer’s own programmatic/descriptive text on the legend of the Matinta and the Curupira, we established a correspondence between that and the musical text, in order to help the interpretation of the work. Then, we identified the technical elements of the violin used in the piece studied. An analysis of the form and of the melodic material was made, in order to understand the context in which these techniques were used. Having as reference the main pedagogical treatises of the Twentieth and Twenty First Centuries, we approached separately and in details, the mechanics of each of the violin techniques used in the piece. Together we also presented short exercises trough images, videos, audios and others musical examples, to help the understanding and study of those referred violin techniques.